Chart review of acute myocardial infarction at a district hospital in KwaZulu-Natal, South Africa - Roland Chetty; Andrew Ross (AOSIS, 2016)
Background: Incidence and prevalence of non-communicable diseases, including ischaemic heart disease (IHD) and associated acute myocardial infarction (AMI), are increasing in South Africa. Local studies are needed as contextual factors, such as healthcare systems, gender and ethnicity, may affect presentation and management. In AMI, reviews on time between onset of chest pain and initiation of urgent treatment are useful, as delays in initiation of thrombolytic treatment significantly increase morbidity and mortality. Aim: The aim of the study was to determine the profile and management of patients admitted with ischaemic chest pain.Setting: The study was carried out in a busy urban-based district hospital in KwaZulu-Natal, South Africa. The population served is poor, and patients are mainly Indian with associated high risk of IHD. Methods: A chart review of all patients seen at the hospital with acute ischaemic chest pain between 01 March and 31 August 2014 was undertaken. Results: More male than female patients were admitted, with a wide variation in age. Most eligible patients received required thrombolytic intervention within an acceptable time period after arrival at hospital. Conclusion: Chest pain and AMI were a relatively common presentation at the study site, and urgent diagnosis and initiation of fibrinolytic therapy are essential. The encouraging door-toneedle time may have been influenced by the availability of specialist family physicians, trained as 'expert generalists' to provide appropriate care in a variety of settings and consultant support to junior staff. The role of the family physician and primary healthcare doctor in primary prevention are re-emphasised through the study findings. Keywords: Acute myocardial infarction; KwaZulu-Natal; district hospital; Asian population; hospital chart review; door-to-needle-time